Investigation of the Association between Computed Tomography Hounsfield Units and Cerebral Infarction Phases: A Cross-sectional Study - Ali, Babar; Hadadi, Ibrahim; Amir, Abdullah; Alamri, Rahaf Saeed; Al-Shahrani, Leen M; Ago, Jacob Leonard; Khalid, Muhammad Ibtsam; Musa, Alamin (Journal of Neonatal Surgery, 2025)
Background and purpose: Cerebral infarction is a severe medical condition that requires accurate diagnosis and management and can be achieved with the used of computed tomography (CT). Hounsfield unit (HU) values measured on CT scans may provide essential information concerning the severity of cerebral infarction. This study investigated the association between the HU values and the severity (phase) of cerebral infarction. Methods: A descriptive cross-sectional design was used to gather data from 102 patients over seven months (August 2023 to February 2024) at the University of Lahore Teaching Hospital after the study had been ethically approved by an institutional review board. HU measurements were made with standardized CT protocol on a 4-slice Toshiba equipment. Data were analyzed descriptively and inferentially to reveal the association between HU measurements and the severity of cerebral infarction (acute, sub-acute, and chronic phases). The inferential statistics included Bayesian ANOVA and one-way ANOVA, assuming significance at p≤0.05. Results: The study found a significant association between the HU values and the severity of cerebral infarction (p<0.000), with the acute phase exhibiting higher mean values (HU=22.31), while the sub-acute and chronic phases followed with HU values of 14.63 and 7.04 respectively. There was a progressive decrease in HU values from the acute phase (HU range = 19 to 25) to the chronic phase (HU values <10). Conclusion: This study identified a significant relationship between the CT phases and the HU values in cerebral infarction. The results show the clinical significance of HU values in potentially diagnosing and managing cerebral infarction. An understanding of the association between the HU measurements and CT phase may be useful in accurately evaluating cerebral infarctions and subsequently make informed decisions regarding patient management and treatment. The results also underscore the importance and potential of HU values in evaluating cerebral infarctions, providing a roadmap for improving patient outcomes in the diagnosis of cerebral infarctions with CT.